Biogeochemical lichen-indication study of the state and dynamics of the atmospheric pollution of the arboretum of the falz-fein biosphere reserve "Askania Nova" - Shabatura, О.; Blum, О.; Тютюнник, Ю.; Шабатура, О.; Блюм, О. (Київський національний університет імені Тараса Шевченка, 2023)
By the method of biogeochemical lichen indication on the territory of the arboretum of the Falz-Fein Biosphere Reserve "Askania-Nova" (Kherson Region, UKRAINE) the temporal trends (2011-2021) in the concentrations of heavy metals and other micro- and macro-elements in the epiphytic lichens was estimated. The lichens samples of Parmelia sulcata, Xanthoria parietina and Evernia prunastri collected in 2011 (39 sites) and 2021 (44 sites) for the concetrations of 22 chemical elements (Al, B, Ba, Ca, Cd, Cr, Co, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, S, Sb, Se, Sr, Ti, V and Zn) by the ICP-OES spectroscopy were analysed. In order to correctly compare the concetrations of elements in different species of lichens, their intercalibration to the base species P. sulcata was carried out and the calibration coefficients, the so-called biogeochemical lichen indicies (BGCHL indicies), were calculated. Based on these indicies the arithmetically averaged hypothetical concetrations of elements in lichen samples collected at the sites, where P. sulcata was absent, were calculated and corresponding databases of element concentrations for all three species were created. Factor analysis was applied to identify possible sources of the elements determined in the lichens for the period of 2011 (Fa-1 – Fa-8) – 2021 (Fb-1 – Fb-8). The eight resulting factors represent crust and anthropogenic components. Some of the factors were interpreted as being associated with the agricultural activities, microclimate, pH of atmospheric precipitation and with the higher plants factor (leaching of  еlements and their absorption by lichens). The factor structure of the chemical elements concetrations in the lichens growing on the studied area was formed under regional conditions of the accumulation of Cr, Na, Ti, as well as a decrease in the concetrations of such elements as V, Zn, Mn, Cu, Mg, K, Sr, Ba, Pb, Ni, Ca, S and Se. Moreover, Sb and Ba have spatially heterogeneous dynamics of their concetrations, and Se has very heterogeneous dynamics with a decreasing trend of the concentrations.

Методом біогеохімічної ліхеноіндикації на території дендропарку Біосферного заповідника ім. Фальц-Фейна "Асканія-Нова" (Херсонська обл., Україна) встановлено часові тренди (2011–2021 рр.) концентрацій важких металів та інших мікро- і макроелементів у епіфітних лишайниках.Зразки лишайників Parmelia sulcata, Xanthoria parietina та Evernia prunastri, зібрані у 2011 (39 точок) та 2021 (44 точки), було проаналізовано на вміст 22 хімічних елементів (Al, B, Ba, Ca, Cd, Cr, Co, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, S, Sb, Se, Sr, Ti, V і Zn) за допомогою методу ICP-OES спектроскопії.Для коректного порівняння концентрацій елементів у різних видах лишайників було проведено їх інтеркалібрування до базового виду P. sulcata та розраховано калібрувальні коефіцієнти, так звані біогеохімічні ліхеноіндикаційні показники (BGCHL показники). На основі цих показників було розраховано середньоарифметичні гіпотетичні концентрації елементів у зразках лишайників, зібраних на ділянках, де P. sulcata була відсутня, та створено відповідні бази даних концентрацій елементів для всіх трьох видів.Для ідентифікації можливих джерел надходження в лишайники визначених елементів за період 2011 (Fa-1 – Fa-8) – 2021 (Fb-1 – Fb-8) років було застосовано факторний аналіз. Вісім отриманих факторів представляють ґрунтовий покрив та антропогенні компоненти. Деякі з факторів були інтерпретовані як такі, що пов'язані із сільськогосподарською діяльністю, мікрокліматом, рН атмосферних опадів і з рослинним фактором (вилуговування елементів з дерев та їх поглинання лишайниками).Факторна структура концентрацій хімічних елементів у лишайниках, що зростають на досліджуваній території, формувалася за умов регіонального накопичення Cr, Na, Ti, а також зниження концентрацій таких елементів, як V, Zn, Mn, Cu, Mg, K, Sr, Ba, Pb, Ni, Ca, S і Se. Крім того, Sb та Ba мають просторово неоднорідну динаміку концентрацій, а Se має дуже неоднорідну динаміку з тенденцією до зменшення.
Біогеохімічне ліхеноіндикаційне вивчення стану та динаміки атмосферного забруднення дендропарку "Асканія-Нова"
Keywords: lichens; biogeochemical lichen indication; micro- and macroelement; heavy metals; air pollution; factor analysis; "Askania-Nova" Biosphere Reserve; лишайники; біогеохімічна ліхеноіндикація; мікро- та макроелементи елементи; важкі метали; забруднення повітря; факторний аналіз; Біосферний заповідник "Асканія-Нова"